2005
DOI: 10.1084/jem.20050707
|View full text |Cite
|
Sign up to set email alerts
|

FASL –844C polymorphism is associated with increased activation-induced T cell death and risk of cervical cancer

Abstract: The FAS receptor–ligand system plays a key role in regulating apoptotic cell death, and corruption of this signaling pathway has been shown to participate in tumor-immune escape and carcinogenesis. We have recently demonstrated (Sun, T., X. Miao, X. Zhang, W. Tan, P. Xiong, and D. Lin. 2004. J. Natl. Cancer Inst. 96:1030–1036; Zhang, X., X. Miao, T. Sun, W. Tan, S. Qu, P. Xiong, Y. Zhou, and D. Lin. 2005. J. Med. Genet. 42:479–484) that functional polymorphisms in FAS and FAS ligand (FASL) are associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
100
4
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 36 publications
12
100
4
2
Order By: Relevance
“…There are many factors involved in the AICD. Fas and FasL are very important proteins in the AICD process [36,37]. Fas is a molecule expressed on activated T cells and serves as an activation marker for T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many factors involved in the AICD. Fas and FasL are very important proteins in the AICD process [36,37]. Fas is a molecule expressed on activated T cells and serves as an activation marker for T cells.…”
Section: Discussionmentioning
confidence: 99%
“…This means that immunization induced Fas expression in T cells, but that the FasL transcription was not upregulated simultaneously. It is well known that high Fas with low FasL will keep the activated T cells resistant to AICD [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMC) from healthy donors were isolated by Ficoll-Paque (GE Healthcare) density-gradient centrifugation as described previously (21). The PBMCs were used for the determination of cancer cell-induced T-cell apoptosis by coculture with lung cancer cells (TL4, A427, H1355, and TL13) at a ratio of 10:1 for 36 hours.…”
Section: Peripheral Blood Monocyte Isolation and Coculture Experimentsmentioning
confidence: 99%
“…A series of case-controlled studies from Lin's group indicated that the functional FasL À844T/C polymorphism in a Chinese population was associated with an increased risk of different human cancers, including those of the cervix, lung, esophagus, breast, and pancreas (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation